Effect of cutting height and growth stage on seasonal forage yield of alfalfa - Costa, Newton de Lucena; de Saibro, João Carlos (Pesquisa Agropecuaria Brasileira, 1992)
A field trial, at Guaíba, RS, was carried out to evaluate the effect of cutting height (5 and 10 cm) and growth stage (vegetative and flowering) on the seasonal forage yield of alfalfa (Medicago sativa L. cv. Crioula), weeds, and crude protein (CP) contents and yields of the total mixture components (alfalfa + weeds). The season significantly (P< 0.05) affected forage production, being the highest dry matter (DM) yields obtained during Spring and Summer for alfalfa, and Summer and Autumn for weeds. Cutting forage at the alfalfa flowering stage at 5 cm stubble height resulted in the highest DM yields of alfalfa and provided a better forage seasonal trends. The DM yields of weeds were improved by the utilization at the vegetative stage at 5 cm stubble height, except on Summer when clipping at flowering stage were more productive. In all seasons, clipping at vegetative stage, at 10 cm stubble height, provided the highest CP contents. During Summer and Spring, clipping at flowering stage resulted in the higher CP yields.